MODEL PEMBELAJARAN NAHWU SERTA IMPLIKASINYA TERHADAP KEMAMPUAN MEMBACA KITAB DI PONDOK PESANTREN ANWARUL HUDA MALANG - Rosyadi, Lalu Imron; Fahresy, M. Haikal Jamil Irgi; Yusufi, Mohammad Zaidani Nur; Rohman, Hamdi Atiqur; Kirami, Ashhabul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2024)
This research is an investigation effort into Nahwu learning at the Anwarul Huda Islamic Boarding School, Malang, in order to find a learning model and its impact on the ability of class 2 of Madrasah Wustho Diniyah Nurul Huda, Anwarul Huda Islamic Boarding School, Malang, in reading. This type of research is qualitative with descriptive methods. The instruments used include: interviews, observation, documentation and tests. The results of the research are that the Nahwu learning model is based on the Teacher Centered Learning approach, thereby reducing the deductive method which begins with the ustaz's activity of interpreting books in Javanese, then providing explanations in Indonesian, and providing opportunities for students to ask questions; and the implemented learning model is able to improve students' ability to read books, but not too significantly.